Antioxidant activity of Garcinia atroviridis Griff. ex T.Anderson - Sura Maan Salim (Caspian Journal of Environmental Sciences)
This study aimed to investigate and evaluate the amount of antioxidants activity and total phenolic contents of the plant Garcinia atroviridis Griff. ex T.Anderson. Only the leaves and fruit were used for this study. These samples were washed, dried and grinded, then Soxhlet apparatus and methanol were used for extraction, and the end products were used for the study. Two methods were used for this study, 2, 2-Diphenyl-1-picrylhydrazyl (DPPH) assay was used to evaluate the antioxidant activity and the second assay was total phenolic content (TPC) to measure the quantity of phenols in leave and fruit extracts. Four standards were used for DPPH assay including ellagic acid, tannic acid, gallic acid and rutin. Their results were then compared with the two samples results. Twelve concentrations were prepared for the standards and samples. The antioxidant activity was expressed as the efficient concentration needed to scavenge 50% of free radicals. For TPC assay, gallic acid was the standards and six concentrations were prepared for the standards and samples. In both methods, microplate reader machine or spectrophotometer was used to read the absorbance. According to the results of both assays, the fruit extract exhibited higher antioxidant activity and higher total phenolic content compared to the leaves extracts. The efficient concentration of fruit extract was 4 mg mL-1, while in the case of leaves extract, it could not be attained. The mean of gallic acid in 1 mg of fruit extracts was 0.070, while in leaves extract was 0.069. It was also concluded that when the concentration increases, antioxidant activity and total phenolic content elevates as well.